SAT0401 Risk of hospital admission due to severe infection in patients under treatment with anti-tnf drugs: data from a local registry. (12th June 2018) - Rosas, J.; Pucciarelli, M.; Senabre-Gallego, J.M.; García-Gómez, J.A.; Ena, J.; Santos-Soler, G.; Barber, X.; Salas, E.; Pons-Bas, A.; Cano, C.; Ivars, E.; Lorente, M.; et al.
Abstract : Objectives: To Know characteristics of patients treated with anti-TNF, who suffered infections that forced hospital admission. Methods: Prospective observational study in patients treated with anti-TNF, during 1/1/2000 to 12/31/2017, followed up in the Rheumatology Section. General data of patients (age, gender), of disease (diagnosis and time of evolution, type of anti-TNF, time in anti-TNF, concomitant treatment with DMARD), regarding the presence of severe infection, defined as infection that required hospital admission (time in anti-TNF to infection, location of infection, days of admission, mantoux/IGRAS and vaccinations prior to the start anti-TNF treatment) was collected. The admission decision was made by Emergency Department of centre or Rheumatology. Results: Of 442 patients with anti-TNF, 44 (9.6%) patients had at least one hospital admission due to severe infection. 59% were women, with mean age 64±16.72 years, 22–88 21.25±4.02 years of disease evolution. A mantoux/IGRAS was performed prior anti-TNF. Diagnosis was: rheumatoid arthritis (RA): 25 (57%), ankylosing spondylitis (AS): 12 (27%), psoriatic arthritis (PSA): 5 (11%) and juvenile idiopathic arthritis (JIA): 2 (5%). The mean time of treatment with anti-TNF is 5.6±4.5 years. Adalimumab received 24 (55%) patient, infliximab 8 (18%) patients, etanercept 6 (14%) patients, golimumab 5 (11%) and 1 (2%) certolizumab. Of the 55 confirmed infections: non-pneumonic infection in 13 (24%) patients, pneumonia: 10 (18%), septic arthritis: 6 (11%), septic shock and/or bacteremia: 6 (11%), abscess: 4 (7%), urinary infections: 4 (7%), cellulitis: 3 (5%), cutaneous leishmaniasis: 3 (5%), acute gastroenteritis: 2 (4%), surgical wound infection: 1 (2%), cutaneous infection: 1 (2%), Septic bursitis: 1 (2%), gonorrhoea: 1 (2%). The mean time of hospital admission was 9.76 days. Three (7%) patients presented the infection within a year of starting treatment. The rate of severe infection x100 patients/year of exposure is 2.01 (1.47–2.67). The odd ratio of admission for infection of 3.67 (1.11–4.87, p=0.03). The risk of admission for infection in patients with peripheral arthritis (RA, PSA, JIA) is 2.42 (1.21–3.11) times higher than in patients with AS (p=0.012). In the table 1, the Odd ratio of income for infection distributed by anti-TNF drug is shown. Conclusions: 1. The severe infection rate x100 patients/year of exposure is 2.01 and the prevalence is 9.6%. 2. The majority of severe infection occurred late, after more than 1 year of treatment. 3. The most frequent infection were those of respiratory origin, followed by sepsis or bacteremia and septic arthritis. 4. Etarnecept has presented the lowest rate of severe infection. 5. Patients with AS have a lower risk of severe infection than patients with chronic peripheral arthritis. Acknowledgements: The study was supported with a research grant from the Association for Research in Rheumatology of Marina Baixa (AIRE-MB). Disclosure of Interest: None declared